METHODS OF FACTOR ANALYSIS OF PROFIT OF ENTERPRISES OF CITY GAS NETWORKS - Kostyuk, V.; Milkin, I. (Municipal economy of cities. Series: «Economy science», 2022)
The article considers the method of calculating the influence of the most important factors on the change in profits of enterprises of city gas networks. It is proposed to use a set of multiplicative economic and mathematical models in the process of factor analysis of this indicator, which contain a number of different factors that characterize the features of the production process and the final financial result of enterprises of city gas networks. To determine the quantitative influence of these factors on the overall change in profit, it is recommended to carry out the step-by-step analysis of this indicator, which is based on the method of network substitutions. This methodological approach allows, depending on the available source information and the purpose of the analysis to calculate the impact on changes in profits of different number of factors, i.e. to perform two-factor, three-factor and multi-factor analysis of this indicator. The presented method of step-by-step factorial analysis of profit allows it to be decomposed into the number of components of primary indicators, presented in the form of deterministic economic and mathematical models, to determine the quantitative influence of the most important factors on the overall change in this indicator for any period of time of operation of the enterprise, to study patterns and individual trends of such influence, to use the obtained analytical information to substantiate and make appropriate management decisions to improve the financial results of the enterprises of city gas networks.